Coronal Magnetometry 2013
DOI: 10.1007/978-1-4939-2038-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Coronal Mass Ejections with the Coronal Multichannel Polarimeter

Abstract: The Coronal Multichannel Polarimeter (CoMP) measures not only the polarization of coronal emission, but also the full radiance profiles of coronal emission lines. For the first time, CoMP observations provide high-cadence image sequences of the coronal line intensity, Doppler shift and line width simultaneously over a large field of view. By studying the Doppler shift and line width we may explore more of the physical processes of the initiation and propagation of coronal mass ejections (CMEs). Here we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…However, another situation that the angular momentum of the jet was passed into that of the CME is not prohibited. As lack of direct observations on the rotational motion of the CME [discussions on this particular issue could be found in Tian et al, 2013, as an example], we could try to figure out if this situation is possible from the poloidal motion of magnetic clouds (MCs) which are the counterpart of CMEs in the interplanetary space. As derived from a velocity-modified cylindrical force-free flux rope model base on Wind observations, Wang et al [2015] found that almost all the MCs more or less had shown poloidal motion with meridian linear speed around 10 km s −1 .…”
Section: Mechanisms and Discussionmentioning
confidence: 99%
“…However, another situation that the angular momentum of the jet was passed into that of the CME is not prohibited. As lack of direct observations on the rotational motion of the CME [discussions on this particular issue could be found in Tian et al, 2013, as an example], we could try to figure out if this situation is possible from the poloidal motion of magnetic clouds (MCs) which are the counterpart of CMEs in the interplanetary space. As derived from a velocity-modified cylindrical force-free flux rope model base on Wind observations, Wang et al [2015] found that almost all the MCs more or less had shown poloidal motion with meridian linear speed around 10 km s −1 .…”
Section: Mechanisms and Discussionmentioning
confidence: 99%
“…viewer with radius). The Doppler measurements shown in Figure 7 incorporate a subtraction of the background coronal rotation using a median filter (Tian et al, 2013), so there is some ambiguity about precisely where flows shift from towards to away in the rotating frame. Nevertheless, there are clearly strong gradients in the flow of coronal plasma within the cavity, with functional dependence on radial distance from cavity center.…”
Section: Open Questionsmentioning
confidence: 99%
“…The full width at half maximum (FWHM) of an optically thin spectral line is given by FWHM=λ0c4log2()2kBTiM+vnth2 where c is the speed of light, λ 0 is the rest wavelength, k B is the Boltzmann constant, T i is the ion temperature, M is the ion mass, and v nth is a nonthermal velocity parameter which describes the unresolved, nonthermal motions of the ion. Line width measurements can thus provide critical information on the location of shocks, of turbulence, of ion heating in both closed and open magnetic field structures, identify subresolution rotating structures, to name a few, as discussed by Tian et al [].…”
Section: Visible Plasma Diagnostic Techniquesmentioning
confidence: 99%
“…These measurements encompass the region where a large fraction of the total energy of the CME event has already been released into CME plasma heating and acceleration. Tian et al [] already showed that such studies are possible.…”
Section: Science Goals That Can Be Addressedmentioning
confidence: 99%